Evaluation of the Nutritive and Organoleptic Values of Food Products Developed by Incorporated Catharanthus roseus (Sadabahar) Fresh Leaves Explore Their Hypoglycemic Potential - Gita Bisla; Shailza Choudhary; Vijeta Chaudhary (The Scientific World Journal)
Diabetes becomes a real problem of public health in developing countries, where its prevalence is increasing steadily. Diabetes mellitus can be found in almost every population in the world. Since the Ayurvedic practice started in India, plants are being used in the cure of diseases. Although the Catharanthus roseus have been used for their alleged health benefits and avail their hypoglycemic effect, used as medicine by diabetics. Medicinal plants have rarely been incorporated in food preparations. To fill these lacunae, food products were prepared by using Catharanthus roseus (Sadabahar) fresh leaves with hypoglycemic properties. Commonly consumed recipes in India are prepared for diabetic patients and were developed at different levels at 3 g, 4 g, and 6 g per serving. Food product development and their acceptability appraisal through organoleptic evaluation were carried out by semitrained panel comprising 15 trained panelists from the department of Food Science and Nutrition, Banasthali University. Seven products were developed by incorporating Catharanthus roseus fresh leaves. Nine point hedonic scale was used as a medium to know about the product acceptability at various variances. All products are moderately acceptable at different concentrations except product fare “6 g” which was more acceptable than the standard. Among the three variations of incorporating the Catharanthus roseus (Sadabahar) Leaves, 3 g variation is more acceptable than other variations.